Benign Endobronchial Inflammatory Polyp with Cystic Degeneration: A Case Report - Kuwal, Ashok (Turk Thorac J, 2019)
Endobronchial lesions causing luminal obstruction are mostly found in bronchogenic carcinoma. Inflammatory polyps originating from the tracheobronchial tree are rarely found. Here we report a case of an elderly male presenting with prolonged cough who was found to have an endobronchial inflammatory polyp. The polyp was resected completely with the use of the flexible bronchoscope and electrocautery snare.